1977
DOI: 10.1901/jaba.1977.10-559
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Gender Development and Psychosocial Adjustment

Abstract: A 5-yr-old boy with pronounced sex-role inflexibility and stereotypic extremes in gender behavior was behaviorally treated by Rekers and Lovaas (1974). Winkler (1977) criticized Rekers and Lovaas for selecting certain feminine sex-typed target behaviors for intervention,2 but he presented neither relevant empiri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 39 publications
0
19
0
2
Order By: Relevance
“…In the area of sexual deviance, preventive studies are limited to attempts to hinder the development of gender identity problems (Rekers, 1977;Rekers & Lovaas, 1974). There are few preventive studies dealing with child molesting (Ballard,Gipson,Lawson,& Telch,Note 1).…”
mentioning
confidence: 99%
“…In the area of sexual deviance, preventive studies are limited to attempts to hinder the development of gender identity problems (Rekers, 1977;Rekers & Lovaas, 1974). There are few preventive studies dealing with child molesting (Ballard,Gipson,Lawson,& Telch,Note 1).…”
mentioning
confidence: 99%
“…Also a Southern Baptist minister, Rekers's research focused on preventing and treating homosexuality in children. 171 In 1983, Rekers co-founded the Family Research Council with James Dobson and a number of other conservative Christian leaders, creating one of America's most influential right-wing lobbying organizations. 172 Rekers served as an officer of the National Association for Research and Therapy of Homosexuality (NARTH), an organization devoted to conversion therapy, until he resigned in 2010 after the media reported that he had hired a gay male prostitute to accompany him on a two week trip to Europe.…”
Section: A Anti-gay and Lesbian Parenting Researchmentioning
confidence: 99%
“…Rosen et al «(977) base this hypothesis on clinical observation of dozens of children. (Rekers, 1977;Rekers & Lovaas, 1974;Rekers et al, 1974;Rekers & Varni, 1977;Rosen & Teague, (974). The first empirical investigation of this theoretical distinction indicated that the two syndromes were separate, though highly correlated (r=o.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…Moreover, they noted that the term 'sissy' is culturally pejorative and that the disadvantages accruing for a child so labelled increase with age. Investigators working in this area are acutely aware of the culture-relative aspects of masculinity and femininity, and of the difference between enjoying activities more typical of the opposite sex and actually believing one is of the opposite sex (Rekers, 1975;Rekers, 1977;Rosen & Rekers, 1975;. It is known that most little boys engage in some feminine play, and most little girls in some masculine play, with no identity conflicts whatsoever (Green, 1976).…”
Section: Therapeutic Interventionmentioning
confidence: 99%